Effects of various brans on quality and volatile compounds of bread - Ahmed M.S. Hussein; Gamil E. Ibrahim (Foods and Raw Materials, 2019)
The present study aimed to evaluate the effect of various bran sources, including wheat, barley, and rice, on the quality and volatile compounds of Egyptian ‘balady’ bread (Fino). The protein, fat, and total carbohydrates content of the studied brans ranged from 8.49 to 14.16%, 2.16 to 8.12%, and 34.38 to 85.06%, respectively. The mi- neral composition and colour parameters of the brans were also evaluated. The substitution of wheat flour with 10%, 20%, and 30% of different brans resulted in decreased loaf volume and specific volume, and increased loaf weight. A significant decrease in colour parameters (L, a, and b) of the bread crust and crumb were observed in all the sam- ples. The addition of bran at three concentrations showed a remarkable increase in the total phenolic content of the bread samples, compared to the control. The antioxidant activity of the bread samples fortified with brans showed the following order: RB (rice bran) > BB (barley bran) > WB (wheat bran), as determined by the DPPH and β-carotene assays. Thirty-six volatile compounds identified in the bread samples using GC-MS included 5 alcohols, 6 pyrazines, 2 acids, 9 aldehydes, 5 ketones, 3 esters, and 6 sulphur-containing compounds. Alcohols were the predominant vola- tile constituents accounting for 58.3; 61.57; 59.08; and 56.15% in the control and in the bread samples prepared with bran from rice, barley, and wheat, respectively.